The pharmacokinetics and pharmacodynamics of single‐dose and multiple‐dose recombinant activated factor VII in patients with haemophilia A or B. Issue 6 (29th August 2017) - Fernández‐Bello, I.; Stenmo, C.; Butta, N.; Lind, V.; Ezban, M.; Jiménez‐Yuste, V.
Summary: Monitoring recombinant activated factor VII (rFVIIa) treatment outcomes remains challenging. Thromboelastography (TEG) and the thrombin generation assay (TGA), measure coagulation dynamics over time and are being assessed as potential methods for evaluating and monitoring haemophilia treatment. Lack of standardized TEG/TGA methods makes it difficult to compare results and to establish a correlation with clinical outcomes. Aims: To compare the pharmacokinetics (PK) of rFVIIa after 3×90 μg kg −1 doses vs a single dose (270 μg kg −1 ) in haemophilia patients and to evaluate TEG/TGA results postdosing to determine how these assays relate to PK findings. Methods: Patients in this open‐label, single‐centre, randomized, crossover trial received one injection of 270 μg kg −1 rFVIIa crossed over with three injections of 90 μg kg −1 rFVIIa in a non‐bleeding state. For TEG, kaolin and tissue factor were used as activators; TGA was performed on frozen platelet‐rich and platelet‐poor plasma, with and without corn trypsin inhibitor. FVIIa activity was evaluated using in vivo samples. Results: TGA showed a dose‐dependent effect of rFVIIa on thrombin generation; TEG revealed lower dose‐dependent effects. Both showed some differences between single‐/multiple‐dose rFVIIa; both supported the PK findings. Conclusion: While TEG and TGA are not yet clinically predictive, both supported the PK results. Data suggest that, while a single dose of 270 μg kg −1 rFVIIa provides slightly higher haemostatic potential than the multiple‐dose regimen of 3×90 μg kg −1, the latter results in prolonged activity levels compared with a higher single dose.